Polymer interface protection layer materials for high voltage lithium batteries and their preparation and application
By using liquid polymer interface protective layer materials formed by polysilsesquioxane, glycidyl ether and polyethylene glycol derivatives in high-voltage lithium batteries, the low cycle efficiency of traditional lithium-ion batteries is solved. and poor safety issues, achieving higher energy density and rate performance.
Patent Information
- Application Number
- CN202410485323.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-22
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-04-22
AI Technical Summary
Traditional lithium-ion batteries have problems such as low cycling efficiency, poor safety and the inability to effectively conduct lithium ions under high voltage conditions, which affects the energy density and rate performance of the battery.
Polysilsesquioxane, glycidyl ether and polyethylene glycol derivatives are used as monomers to form a liquid polymer interface protective layer material through thermal polymerization, and a protective layer is coated on the electrode surface of a high-voltage lithium battery.
The mechanical strength and lithium ion conduction capability of the polymer interface protective layer are improved, and the positive electrode stress deformation and negative electrode lithium dendrites are effectively suppressed, which improves the cycle stability and safety performance of the battery.
Smart Images

Figure CN118173789B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrochemical energy storage materials, and in particular to polymer interface protection layer materials for high-voltage lithium batteries and preparation and application thereof. Background Art
[0002] Lithium-ion batteries have attracted widespread attention due to their outstanding advantages such as high operating voltage, low self-discharge, environmental protection and long cycle life. However, with the growing demand for portable computers, smart phones, and automotive batteries, traditional lithium-ion batteries can no longer meet the demand for higher energy density in high-end devices due to the relatively low theoretical capacity of their positive and negative electrode materials.
[0003] Lithium metal has the lowest redox potential (-3.04V) and extremely high theoretical specific capacity (3860mAh / g). Therefore, using lithium metal directly as the negative electrode of lithium secondary batteries and matching it with a high-voltage high-nickel ternary positive electrode can greatly improve the energy density of lithium batteries. However, such batteries cannot be commercialized due to their low cycle efficiency and poor safety. On the positive electrode side, the electrolyte continues to oxidize and decompose under high voltage conditions; the high-nickel ternary material will cause structural damage and reduced cycle performance when it is in a lithium-free state; during the charge and discharge process, due to the multivalent state changes and volume changes of elements such as nickel and cobalt, cracks are easily generated in the secondary particles, accelerating the consumption of the electrolyte. On the negative electrode side, lithium ions will cause dendrite growth during deposition, which can penetrate the diaphragm and cause internal short circuits in the battery; electrolyte components and lithium metal will continue to react with side effects, wrapping the dendrites to cause "dead lithium", thereby increasing the interface resistance; the unstable interface causes the volume of lithium metal to change infinitely, ultimately causing metal lithium to pulverize and even short circuit danger.
[0004] Introducing a polymer interface protection layer is an effective way to stabilize battery cycles. While blocking the continuous side reactions between the electrolyte and the electrode, the polymer interface layer is used to alleviate the volume changes of the positive and negative electrodes during the charge and discharge process. However, in conventional polymers, lithium ions move through the combination and dissociation of organic polymer segments. However, conventional polymers such as polyethylene oxide, polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, etc. have a high degree of crystallinity, which limits the ability of polymer segments to conduct lithium ions. The interface protection layer cannot effectively conduct lithium ions, thereby affecting the conductivity of the battery and reducing the battery's rate performance. In addition, conventional polymer protective films have poor mechanical strength and cannot inhibit the growth of lithium dendrites.
[0005] To this end, the present invention provides a polymer interface protection layer material for a high-voltage lithium battery and a preparation method and application thereof. Summary of the invention
[0006] In order to solve the deficiencies in the above-mentioned prior art, the present invention provides a polymer interface protection layer material for a high-voltage lithium battery and its preparation and application. The present invention is directed to a polymer interface protection layer formed on the electrode surface of a high-voltage lithium battery. In order to improve the uniform formation of the polymer interface protection layer on the electrode surface and to improve the protective effect of the polymer interface protection layer on the electrode surface, the present invention is prepared in a solution environment, which can not only improve the polymerization efficiency between each monomer and promote the formation of polymers, but also the obtained material is in a liquid state, and there is no need to post-treat the liquid material. It can be directly applied to the electrode surface of the high-voltage lithium battery that needs to be protected. After drying and removing excess solvent, a polymer interface protection layer can be formed on the electrode surface of the high-voltage lithium battery.
[0007] The polymer interface protection layer material of a high voltage lithium battery and the preparation method thereof of the present invention are realized by the following technical scheme:
[0008] The first object of the present invention is to provide a method for preparing a polymer interface protection layer material for a high voltage lithium battery, comprising the following steps:
[0009] Step 1: using polysilsesquioxane, glycidyl ether and polyethylene glycol derivative as monomers, mixing polysilsesquioxane, glycidyl ether, polyethylene glycol derivative, initiator and soluble lithium salt in an organic solvent to obtain a mixed solution.
[0010] It should be noted that the present invention uses polysilsesquioxane, glycidyl ether and polyethylene glycol derivatives as monomers. Under the action of an initiator, the monomers are connected to form a high molecular polymer through condensation of functional groups such as double bonds, epoxy, amino, carboxyl or thiol at the ends of the monomers. Due to the presence of multiple functional groups, the high molecular polymer can form a three-dimensional network structure. The addition of soluble lithium salts increases the number of lithium ions that can be conducted inside the polymer. At the same time, the soluble lithium salts act as additional fillers to reduce the crystallinity of the polymer, thereby further improving the lithium ion conduction ability of the polymer.
[0011] The glycidyl ether used in the present invention is a side chain epoxy structure, which can improve the lithium ion transmission capacity by relying on the swing of the side chain; polysilsesquioxane has multiple functional groups, and the formed polymer is a cross-linked structure, but excessive cross-linking affects the movement of the internal chain segments of the polymer; polyethylene glycol derivatives are the main body of the polymer, and too little use will lead to the formation of oligomers. In order to ensure that polysilsesquioxane, glycidyl ether and polyethylene glycol derivatives can form a high molecular polymer with a certain degree of cross-linking and a certain lithium ion transmission capacity, in a preferred embodiment of the present invention, the mass ratio of the polysilsesquioxane, glycidyl ether and polyethylene glycol derivative is 1:5~50:10~100.
[0012] The polysilsesquioxane used in the present invention has multiple functional groups, and the formed polymer is a cross-linked structure, but excessive cross-linking affects the movement of the internal segments of the polymer, so the degree of cross-linking needs to be controlled. In order to ensure that the polysilsesquioxane, glycidyl ether and polyethylene glycol derivatives can form a cross-linked structure in an organic solvent without affecting the movement of the internal segments of the polymer, in a preferred embodiment of the present invention, the mass ratio of polysilsesquioxane to the organic solvent is 1wt% to 20wt%:1. Among them, the present invention does not limit the specific type of organic solvent used in the above cross-linking process, as long as it can have good solubility for polysilsesquioxane, glycidyl ether and polyethylene glycol derivatives. For example, in another preferred embodiment of the present invention, the organic solvent used is any one of acetone, N,N-dimethylacetamide, dimethyl sulfoxide, tetrahydrofuran, dichloromethane, trichloromethane, and N-methylpyrrolidone.
[0013] In order to improve the mechanical strength of the final polymer protective layer, the present invention preferably uses polysilsesquioxane as a monomer. The polysilsesquioxane has a multifunctional site and can react with other monomers to form a cross-linked structure, thereby improving the mechanical strength of the polymer protective layer, thereby effectively inhibiting positive electrode stress deformation and negative electrode lithium dendrites. And in order to ensure that the polysilsesquioxane used can achieve the above-mentioned effect, in a preferred embodiment of the present invention, the polysilsesquioxane used can be selected from any one of octaamino cage polysilsesquioxane, octacarboxyl cage polysilsesquioxane, octaepoxy cage polysilsesquioxane, octamercapto cage polysilsesquioxane, octahydroxy cage polysilsesquioxane, octavinyl cage polysilsesquioxane, and octaphenyl cage polysilsesquioxane.
[0014] In order to promote the transmission of lithium ions, in a preferred embodiment of the present invention, glycidyl ester is used as a monomer. The molecular structure of glycidyl ester has abundant ether oxygen, epoxy and carbonyl oxygen functional groups, which can serve as binding sites for lithium ions, thereby effectively promoting the transmission of lithium ions. And in order to ensure that the glycidyl ester used can achieve the above effect, in a preferred embodiment of the present invention, the glycidyl ether used is any one of allyl alcohol glycidyl ether, methacrylate glycidyl ether, acrylic acid glycidyl ether, allyl glycidyl ether, and propargyl glycidyl ether.
[0015] In order to further promote the transmission of lithium ions, in a preferred embodiment of the present invention, polyethylene glycol derivatives are used as another raw material. The molecular structure of polyethylene glycol derivatives has rich ether oxygen, epoxy and carbonyl oxygen functional groups, which can be used as binding sites for lithium ions and can synergize with glycidyl esters to further promote the transmission of lithium ions. At the same time, the polyethylene glycol derivatives used in the present invention are flexible polymer segments, which can be used as positive electrode material protective layers and negative electrode material protective layers at the same time, and can effectively alleviate the volume changes generated by the positive and negative electrodes during the charge and discharge process, release stress, and thus protect the electrode structure from damage. And in order to ensure that the polyethylene glycol derivatives used can achieve the above effects, in a preferred embodiment of the present invention, the polyethylene glycol derivatives used are any one of polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, diamino polyethylene glycol, dicarboxyl polyethylene glycol, dimercapto polyethylene glycol, and polyethylene glycol diglycidyl ether.
[0016] The present invention takes into account the insufficient lithium ion conductivity, and therefore chooses to add a soluble lithium salt to reduce the crystallinity of the polymer while improving the lithium ion transmission capacity. In a preferred embodiment of the present invention, the soluble lithium salt used is one or more of lithium perchlorate, lithium difluorooxalatoborate, lithium tetrafluoroborate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, and lithium nitrate.
[0017] In order to ensure that the added soluble lithium salt can achieve the above-mentioned effect, in a preferred embodiment of the present invention, the amount of the soluble lithium salt is 5wt% to 30wt% of the total mass of the mixed solution.
[0018] In order to ensure that the initiator can initiate the polymerization reaction between the above-mentioned monomers, in a preferred embodiment of the present invention, the amount of the initiator is 0.2wt% to 2wt% of the total mass of the mixed solution. In order to ensure that the initiator used can initiate the polymerization reaction between the above-mentioned monomers, in another preferred embodiment of the present invention, the initiator used is one or more of azobisisobutyronitrile, azobisisoheptanenitrile, diisotoluene peroxide, and benzoyl peroxide.
[0019] It should also be noted that, in order to further fully cross-link each monomer, in a preferred embodiment of the present invention, polysilsesquioxane and glycidyl ester are first placed in an organic solvent and mixed to obtain solution A. In order to ensure that polysilsesquioxane and glycidyl ester can be fully dissolved in the organic solvent, the present invention adopts stirring to dissolve the two monomers polysilsesquioxane and glycidyl ester, and in order to improve the dissolution efficiency of polysilsesquioxane and glycidyl ester, stirring can be performed at a temperature of 30 to 60°C until the solution is clear, which means that polysilsesquioxane and glycidyl ester are fully dissolved. Then, polyethylene glycol derivatives and initiators are added to the solution A obtained above and mixed thoroughly to obtain solution B. In order to fully disperse or dissolve the added polyethylene glycol derivative and initiator in the above solution A, the present invention adopts stirring to fully dissolve the polyethylene glycol derivative and initiator, and in order to improve the dissolution efficiency of the polyethylene glycol derivative and the initiator, stirring can be performed at a temperature of 30 to 60°C until the solution is clear, which means that the polyethylene glycol derivative and the initiator are fully dissolved. Finally, a soluble lithium salt is added to the obtained solution B and stirred until the solution is clear, so as to introduce lithium ions into the polymer through the soluble lithium salt and thus improve the ion conductivity of the polymer.
[0020] Step 2, heating the mixed solution to allow the monomers in the mixed solution to undergo thermal polymerization to obtain a polymer interface protection layer material.
[0021] In order to ensure that the above-mentioned concentrated monomers can undergo polymerization reaction, in a preferred embodiment of the present invention, the monomers in the mixed solution are thermally polymerized by heating, and the components undergo free radical-initiated addition polymerization or condensation reaction during the heat-induced polymerization reaction (i.e., thermal polymerization), so that the organic monomers are connected to form a high molecular polymer, and finally a cross-linked high molecular polymer having a cross-linked structure and capable of conducting lithium ions is obtained, that is, a polymer interface protection layer material is obtained, and the temperature of the heating treatment is 40 to 100°C.
[0022] The second object of the present invention is to provide a polymer interface protection layer material for a high-voltage lithium battery prepared by the above preparation method.
[0023] The third object of the present invention is to provide an application of the polymer interface protection layer of the high voltage lithium battery as the polymer interface protection layer of the high voltage lithium battery, and the polymer interface protection layer material is coated on the electrode surface of the high voltage lithium battery, and after drying, the polymer interface protection layer is formed on the electrode surface of the high voltage lithium battery. The coating amount of the polymer interface protection layer material is 0.01-1 g / cm 2; and the thickness of the solid polymer interface protection layer obtained after drying is 500nm~30μm.
[0024] It should be noted that since the present invention is directed to a polymer interface protection layer formed on the electrode surface of a high-voltage lithium battery, in order to improve the uniform formation of the polymer interface protection layer on the electrode surface and to enhance the protective effect of the polymer interface protection layer on the electrode surface, the present invention is prepared in a solution environment, which can not only improve the polymerization efficiency between the monomers and promote the formation of polymers, but also the obtained material is in liquid form, and there is no need to post-treat the liquid material, and it can be directly coated on the electrode surface of the high-voltage lithium battery that needs protection. After drying and removing excess solvent, a polymer interface protection layer can be formed on the electrode surface of the high-voltage lithium battery.
[0025] The present invention does not limit the specific drying method, as long as the excess solvent in the polymer interface protection layer material coated on the electrode surface of the high-voltage lithium battery can be removed to form a solid polymer interface protection layer. For example, the drying temperature is 40 to 100° C. and the heating time is 2 to 24 hours.
[0026] It should also be noted that the electrodes of the high voltage lithium battery of the present invention include a positive electrode and a negative electrode, wherein the positive electrode is a high nickel ternary positive electrode and the negative electrode is a lithium metal negative electrode. That is, the polymer interface protection layer material is coated on the positive electrode surface and the lithium metal negative electrode surface of the high voltage lithium battery.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] The present invention uses polysilsesquioxane, glycidyl ether and polyethylene glycol derivatives as monomers, mixes them with an initiator and a soluble lithium salt in an organic solvent, and then forms a liquid polymer interface protection layer material through thermal polymerization. The liquid polymer interface protection layer material can be easily coated on the electrode surface of a high-voltage lithium battery that needs to be protected. After drying and removing excess solvent, a polymer interface protection layer can be formed on the electrode surface of the high-voltage lithium battery.
[0029] The polysilsesquioxane used in the present invention has multi-functional sites and can react with other monomers to form a cross-linked structure, thereby increasing the mechanical strength of the polymer protective layer and effectively inhibiting positive electrode stress deformation and negative electrode lithium dendrites.
[0030] The polyethylene glycol derivatives and glycidyl esters selected in the present invention have abundant ether oxygen, epoxy and carbonyl oxygen functional groups in their molecular structures, which can serve as binding sites for lithium ions and effectively promote the transmission of lithium ions.
[0031] The polyethylene glycol derivative selected in the present invention is a flexible polymer chain segment, which can be used as a positive electrode material protective layer and a negative electrode material protective layer at the same time, and can effectively alleviate the volume change of the positive electrode and the negative electrode during the charge and discharge process, release stress and thus protect the electrode structure from damage.
[0032] And the polymer interface protection layer material prepared by the present invention can be simultaneously applied to the polymer protection layer on the high voltage positive electrode and the lithium metal negative electrode. The prepared protection layer is a flexible cross-linked polymer protection layer. The oxygen-containing functional groups inside the molecule can promote the transmission of lithium ions. The flexible polymer chain effectively buffers the volume changes of the positive and negative electrode materials during the charging and discharging process and releases the reaction stress. On the positive electrode side, the prepared polymer protection layer can effectively prevent the positive electrode plate from cracking and ensure the structural stability of the positive electrode during the cycle process; on the negative electrode side, the prepared polymer protection layer can effectively inhibit the growth of lithium dendrites, promote the uniform deposition of lithium ions, protect lithium metal from side reactions with the electrolyte, and effectively improve the cycle stability and safety performance of the lithium metal battery.
[0033] The cross-linked polymer prepared by the present invention can be used as both the positive electrode interface protection layer (artificial CEI film) and the negative electrode interface protection layer (artificial SEI film). The polymer protective layer contains abundant functional groups for conducting lithium ions, which can improve the conduction rate of lithium ions in the polymer. On the positive electrode side, the oxidative decomposition of the electrolyte in the high voltage area can be prevented, the volume change of the high-nickel ternary electrode material can be alleviated, and the generation of cracks can be prevented. On the negative electrode side, the prepared cross-linked polymer coating can effectively inhibit the growth of lithium dendrites and prevent further reaction between metallic lithium and the electrolyte, thereby inhibiting the pulverization of lithium metal. This improves the cycle life and safety performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a physical picture of the negative electrode with a polymer protective layer prepared in Example 1.
[0035] Figure 2 This is a scanning electron microscope image of the high-nickel ternary positive electrode with a polymer protective layer prepared in Example 1.
[0036] Figure 3 The infrared spectra of the polymer protective layer materials prepared in Example 1 and Comparative Example 1 are shown.
[0037] Figure 4 This is a rate performance test diagram of a lithium-lithium symmetric battery containing a polymer protective layer prepared in Example 1 and Comparative Example 1.
[0038] Figure 5The high nickel ternary NCM811 positive electrode with a cross-linked polymer protective layer prepared in Example 1 is assembled into a button cell with a lithium metal negative electrode with a polymer protective layer prepared in Example 1; wherein the positive electrode loading is 10 mg / cm 2 .
[0039] Figure 6 The cycling performance diagram of the high nickel ternary NCM811 positive electrode with a cross-linked polymer protective layer prepared in Example 1 and the lithium metal negative electrode with a polymer protective layer prepared in Example 1, wherein the positive electrode loading is 20 mg / cm 2 .
[0040] Figure 7 This is a scanning electron microscope cross-sectional view of the lithium metal negative electrode containing a cross-linked polymer protective layer prepared in Example 1 after cycling.
[0041] Figure 8 This is a scanning electron microscope cross-sectional view of the lithium metal negative electrode prepared in Comparative Example 1 without a cross-linked polymer protective layer after cycling. DETAILED DESCRIPTION
[0042] The technical solutions in the embodiments of the present invention will be described clearly and completely below. It should be noted that the lithium metal negative electrode used in the following embodiments of the present invention is a circular lithium sheet with a thickness of 200 μm and a diameter of 16 mm obtained by cutting a lithium strip with a size of 13 cm × 6 cm × 200 μm. The positive high nickel ternary positive electrode used is NCM811 with a diameter of 8 mm.
[0043] Example 1
[0044] This embodiment provides a polymer protective layer for a lithium metal battery, and the preparation method thereof is as follows:
[0045] (1) 0.05 g of octavinyl polysilsesquioxane was weighed and dissolved in 2 mL of tetrahydrofuran, and then 1 g of glycidyl methacrylate was added to the solution, and a uniform and transparent solution A was obtained after stirring.
[0046] (2) Add 3 g of polyethylene glycol diacrylate and 0.005 g of azobisisobutyronitrile to the solution A obtained in step (1), and stir thoroughly to obtain a solution B.
[0047] (3) Weigh 0.3 g of lithium bis(fluorosulfonyl)imide and 0.1 g of lithium difluorooxalatoborate and add them to solution B of step (2), followed by thorough stirring at 50° C. for 1 h to allow the components to be fully cross-linked, thereby obtaining a cross-linked reaction solution, i.e., a polymer interface protective layer material.
[0048] The polymer interface protection layer material obtained in this example is uniformly coated on the surface of the lithium metal negative electrode and the surface of the high nickel ternary positive electrode, and the coating amount is 0.1 g / cm 2 , and then heated and dried on a 60°C heating table to obtain a negative electrode with a polymer protective layer and a high-nickel ternary positive electrode with a polymer protective layer, respectively.
[0049] Example 2
[0050] This embodiment provides a polymer protective layer for a lithium metal battery, and the preparation method thereof is as follows:
[0051] (1) 0.03 g of octaaminopolysilsesquioxane was weighed and dissolved in 3 mL of dimethyl sulfoxide, and then 1.5 g of allyl alcohol glycidyl ether was added to the solution, and a uniform and transparent solution A was obtained after stirring.
[0052] (2) Add 2 g of polyethylene glycol diacrylate and 0.01 g of azobisisoheptanenitrile to solution A in step (1), and stir thoroughly to obtain solution B.
[0053] (3) Weigh 0.2 g of lithium perchlorate and 0.1 g of lithium tetrafluoroborate and add them to solution B in step (2), and stir them at 40° C. for 0.5 h to allow the components to fully crosslink, thereby obtaining a crosslinking reaction solution, i.e., a polymer interface protective layer material.
[0054] The polymer interface protection layer material obtained in this example is uniformly coated on the surface of the lithium metal negative electrode and the surface of the high nickel ternary positive electrode, and the coating amount is 0.02 g / cm 2 , and then heated and dried on a 70°C heating table to obtain a negative electrode with a polymer protective layer and a high-nickel ternary positive electrode with a polymer protective layer, respectively.
[0055] Example 3
[0056] This embodiment provides a polymer protective layer for a lithium metal battery, and the preparation method thereof is as follows:
[0057] (1) 0.06 g of octaepoxy polysilsesquioxane was weighed and dissolved in 1 mL of N,N-dimethylformamide, and then 0.8 g of polyethylene glycol diglycidyl ether was added to the solution. After stirring, a uniform and transparent solution A was obtained.
[0058] (2) Add 4 g of polyethylene glycol dimethacrylate and 0.008 g of diisotoluene peroxide to solution A in step (1), and stir thoroughly to obtain solution B.
[0059] (3) Weigh 0.25 g of lithium bis(trifluoromethylsulfonyl)imide and 0.1 g of lithium perchlorate tetrafluoroborate and add them to solution B of step (2), and stir them at 50° C. for 0.5 h to fully crosslink the components to obtain a crosslinking reaction solution, i.e., a polymer interface protective layer material.
[0060] The polymer interface protection layer material obtained in this example is uniformly coated on the surface of the lithium metal negative electrode and the surface of the high nickel ternary positive electrode, and the coating amount is 0.05 g / cm 2 , and then heated and dried on a 50°C heating table to obtain a negative electrode with a polymer protective layer and a high-nickel ternary positive electrode with a polymer protective layer, respectively.
[0061] Example 4
[0062] This embodiment provides a polymer protective layer for a lithium metal battery, and the preparation method thereof is as follows:
[0063] (1) 0.06 g of octamercapto polysilsesquioxane was weighed and dissolved in 2 mL of acetone, and then 1 g of allyl alcohol glycidyl ether was added to the solution, and a uniform and transparent solution A was obtained after stirring.
[0064] (2) Add 3 g of diaminopolyethylene glycol and 0.005 g of azobisisobutyronitrile to solution A in step (1), and stir thoroughly to obtain solution B.
[0065] (3) Weigh 0.2 g of lithium tetrafluoroborate and 0.1 g of lithium tetrafluoroborate of lithium bis(fluorosulfonyl)imide and add them to solution B of step (2), and stir them at 50° C. for 0.5 h to fully crosslink the components to obtain a crosslinking reaction solution, i.e., a polymer interface protective layer material.
[0066] The polymer interface protection layer material obtained in this example is uniformly coated on the surface of the lithium metal negative electrode and the surface of the high nickel ternary positive electrode, and the coating amount is 0.1 g / cm 2 , and then heated and dried on a 60°C heating table to obtain a negative electrode with a polymer protective layer and a high-nickel ternary positive electrode with a polymer protective layer, respectively.
[0067] Example 5
[0068] This embodiment provides a polymer protective layer for a lithium metal battery, and the preparation method thereof is as follows:
[0069] (1) 0.06 g of octahydroxypolysilsesquioxane was weighed and dissolved in 2 mL of tetrahydrofuran, and then 0.8 g of glycidyl acrylate was added to the solution, and a uniform and transparent solution A was obtained after stirring.
[0070] (2) Add 2 g of dicarboxyl polyethylene glycol and 0.01 g of azobisisobutyronitrile to solution A in step (1), and stir thoroughly to obtain solution B.
[0071] (3) Weigh 0.35 g of lithium bis(fluorosulfonyl)imide and 0.05 g of lithium tetrafluoroborate of lithium perchlorate and add them to solution B in step 3), and stir them at 40° C. for 2 h to fully crosslink the components to obtain a crosslinking reaction solution, i.e., a polymer interface protective layer material.
[0072] The polymer interface protection layer material obtained in this example is uniformly coated on the surface of the lithium metal negative electrode and the surface of the high nickel ternary positive electrode, and the coating amount is 0.08 g / cm 2 , and then heated and dried on a 60°C heating table to obtain a negative electrode with a polymer protective layer and a high-nickel ternary positive electrode with a polymer protective layer, respectively.
[0073] Comparative Example 1
[0074] The comparative example provides a polymer protective layer for a lithium metal battery, and the preparation method thereof is as follows:
[0075] (1) Weigh 1 g of glycidyl methacrylate and dissolve it in 2 mL of tetrahydrofuran. Stir to obtain a uniform and transparent solution A.
[0076] (2) Add 3 g of polyethylene glycol diacrylate and 0.005 g of azobisisobutyronitrile to solution A in step (1), and stir thoroughly to obtain solution B.
[0077] (3) Weigh 0.3 g of lithium bis(fluorosulfonyl)imide and 0.1 g of lithium difluorooxalatoborate and add them to solution B in step 3), and stir them at 50° C. for 1 h to fully crosslink the components to obtain a crosslinking reaction solution, i.e., a polymer interface protective layer material.
[0078] The polymer interface protection layer material obtained in this example is uniformly coated on the surface of the lithium metal negative electrode and the surface of the high nickel ternary positive electrode, and the coating amount is 0.1 g / cm 2 , and then heated and dried on a 60°C heating table to obtain a negative electrode with a polymer protective layer and a high-nickel ternary positive electrode with a polymer protective layer, respectively.
[0079] That is, the difference between this comparative example and Example 1 is only that:
[0080] In this comparative example, no polysilsesquioxane was added.
[0081] Experimental Section
[0082] (I) Morphology test
[0083] (1) Macromorphology test
[0084] The present invention takes the negative electrode with a polymer protective layer formed by coating the polymer interface protective layer material prepared in Example 1 on the surface of the lithium metal negative electrode and then drying it as an example, and tests its macroscopic morphology, and the test results are as follows: Figure 1 shown.
[0085] A physical picture of the negative electrode with a polymer protective layer prepared in Example 1, and composed of Figure 1 It can be seen that there is an obvious polymer protective layer on the lithium strip, indicating that a lithium metal negative electrode with polymer protection has been successfully prepared, indicating that the polymer interface protection layer material prepared by the present invention can be applied to the negative electrode and used as a solid polymer protective layer of the negative electrode.
[0086] (2) Micromorphology test
[0087] The present invention takes the high nickel ternary positive electrode with a polymer protective layer formed by coating the polymer interface protective layer material prepared in Example 1 on the surface of the high nickel ternary positive electrode and drying it as an example, and tests its microscopic morphology, and the test results are as follows: Figure 2 shown.
[0088] Figure 2 is a scanning electron microscope image of a high nickel ternary positive electrode with a polymer protective layer prepared in Example 1 and is Figure 2 It can be seen that the surface of the high-nickel ternary positive electrode plate has an obvious polymer protective layer, indicating that a high-nickel ternary positive electrode with polymer protection has been successfully prepared, indicating that the polymer interface protection layer material prepared by the present invention can be applied to the positive electrode and used as a solid polymer protective layer of the positive electrode.
[0089] (II) Infrared spectrum test
[0090] The present invention takes the polymer interface protection layer materials prepared in Example 1 and Comparative Example 1 as examples, and performs infrared spectrum tests on them respectively, and the test results are as follows: Figure 3 shown.
[0091] Figure 3 is the infrared spectra of the polymer protective layer materials prepared in Example 1 and Comparative Example 1, and Figure 3 It can be seen that the polymer protective layer materials prepared in Example 1 and Comparative Example 1 do not have any peaks of excess carbon-carbon double bond functional groups, indicating that the polymerization process is complete and a high molecular polymer is formed. If there is a peak of carbon-carbon double bond, it means that the polymerization is incomplete.
[0092] (III) Rate performance test
[0093] (1) Lithium symmetrical battery
[0094] The present invention uses the following method to assemble the negative electrodes with polymer protective layers obtained in Example 1 and Comparative Example 1 to form lithium-lithium symmetrical batteries, and test their rate performances respectively. The test results are as follows: Figure 4 shown.
[0095] Test method: A lithium sheet with a polymer protective layer and a diameter of 12 mm was used. The electrolyte was 1M LiPF6 dissolved in a mixed solution of EC and DEC in a volume ratio of 1:1 and an electrolyte with 5% FEC added. The diaphragm was a PP diaphragm (polypropylene diaphragm), and the battery shell model was CR2032.
[0096] Test conditions: at current densities of 1, 2, 3, 4, 5, 6, and 8 mA / cm 2 Under the conditions of charge and discharge, the battery is cycled 10 times.
[0097] And by Figure 4 The test results show that the polarization voltage of the lithium-lithium symmetrical battery assembled in Example 1 is lower than that of Comparative Example 1 at the same current density. This may be because Example 1 can form a polymer protective layer after adding polysilsesquioxane relative to Comparative Example 1, so it has a smaller polarization voltage. This also shows that polysilsesquioxane plays an important role in forming a polymer protective layer and thus improving the electrochemical performance of the electrode material.
[0098] (2) Button battery
[0099] The present invention assembles the negative electrode with a polymer protective layer and the high nickel ternary positive electrode with a polymer protective layer obtained in Example 1 into a button battery according to the following method, and tests the rate performance thereof respectively, and the test results are as follows: Figure 5 shown.
[0100] Test method: A lithium sheet with a polymer protective layer and a diameter of 12 mm was used. The electrolyte was 1M LiPF6 dissolved in a mixed solution of EC and DEC in a volume ratio of 1:1 and an electrolyte with 5% FEC added. The diaphragm was a PP diaphragm (polypropylene diaphragm), and the battery shell model was CR2032.
[0101] Test conditions: Charge and discharge tests were performed at current densities of 0.2, 0.5, 1, 2, 3, and 4C (1C = 200mAh / g). The NCM811 electrode used had a loading of 10mg / cm 2 The charge and discharge voltage range is 3.0~4.3V.
[0102] And by Figure 5From the test results, it can be seen that the negative electrode with a polymer protective layer obtained in Example 1 and the high-nickel ternary positive electrode with a polymer protective layer are assembled to form a button battery, which has good rate performance at any current density.
[0103] (IV) Cycle performance test
[0104] The present invention uses the negative electrode with a polymer protective layer obtained in Example 1 as the negative electrode, and uses the high nickel ternary positive electrode with a polymer protective layer obtained in Example 1 as the positive electrode, and tests its cycle performance according to the following test method, and the test results are as follows Figure 6 shown.
[0105] Test method: A lithium sheet with a polymer protective layer and a diameter of 12 mm was used. The electrolyte was 1M LiPF6 dissolved in a mixed solution of EC and DEC in a volume ratio of 1:1 and an electrolyte with 5% FEC added. The diaphragm was a PP diaphragm (polypropylene diaphragm), and the battery shell model was CR2032.
[0106] Test conditions: The first two cycles were charged and discharged at a rate of 0.1C to activate the battery, and then the charge and discharge cycle test was performed at a rate of 0.5C. The NCM811 electrode used had a loading of 20mg / cm 2 The charge and discharge voltage range is 3.0~4.3V.
[0107] And by Figure 6 The test results show that after 500 cycles, the battery assembled in Example 1 still has a specific capacity retention rate of 75%, indicating that the prepared polymer protective layer can enable the battery to cycle stably.
[0108] (V) Microstructure after cycle testing
[0109] The present invention takes the negative electrode with a polymer protective layer of Example 1 and Comparative Example 1 as examples, and performs microscopic morphology tests on the materials after the cycles, and the test results are as follows: Figure 7 and Figure 8 shown.
[0110] in, Figure 7 This is a scanning electron microscope cross-sectional view of the lithium metal negative electrode containing a cross-linked polymer protective layer prepared in Example 1 after cycling. Figure 8 This is a scanning electron microscope cross-sectional view of the lithium metal negative electrode prepared in Comparative Example 1 without a cross-linked polymer protective layer after cycling.
[0111] And by Figure 7 and Figure 8The test results show that the surface dendrites of the lithium metal negative electrode without any protection grow severely after cycling, and the electrode structure is severely damaged, while the surface of the lithium metal negative electrode with a polymer protective layer remains smooth and flat after cycling, and the electrode structure is retained.
[0112] Obviously, the above embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
Claims
1. A method for preparing a polymer interface protective layer material for a high voltage lithium battery, characterized in that: The following steps are involved: Taking polysilsesquioxane, glycidyl ether and polyethylene glycol derivative as monomers, polysilsesquioxane, glycidyl ether, polyethylene glycol derivative, initiator and soluble lithium salt are mixed in an organic solvent to obtain a mixed solution; The mixed solution is heated at 40-100° C. to allow the monomers in the mixed solution to undergo thermal polymerization to obtain a polymer interface protection layer material; The mass ratio of the polysilsesquioxane, glycidyl ether and polyethylene glycol derivative is 1:5-50:10-100; The mass ratio of the polysilsesquioxane to the organic solvent is 1wt% to 20wt%:1; The amount of the soluble lithium salt is 5wt% to 30wt% of the total mass of the mixed solution; The glycidyl ether is one of allyl alcohol glycidyl ether, methacrylate glycidyl ether, acrylic acid glycidyl ether, allyl glycidyl ether and propargyl glycidyl ether.
2. The preparation method according to claim 1, characterized in that The amount of the initiator used is 0.2 wt% to 2 wt% of the total mass of the mixed solution.
3. The preparation method according to claim 1, characterized in that: The polysilsesquioxane type is any one of octaamino cage-type polysilsesquioxane, octacarboxyl cage-type polysilsesquioxane, octaepoxy cage-type polysilsesquioxane, octamercapto cage-type polysilsesquioxane, octahydroxy cage-type polysilsesquioxane, octavinyl cage-type polysilsesquioxane, and octaphenyl cage-type polysilsesquioxane.
4. The preparation method according to claim 1, characterized in that: The polyethylene glycol derivative is one of polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, diamino polyethylene glycol, dicarboxyl polyethylene glycol, dimercapto polyethylene glycol, and polyethylene glycol diglycidyl ether.
5. The preparation method according to claim 1, characterized in that: The initiator is one or more of azobisisobutyronitrile, azobisisoheptanenitrile, diisotoluene peroxide, and benzoyl peroxide.
6. A polymer interface protection layer material for a high voltage lithium battery prepared by the preparation method according to any one of claims 1 to 5.
7. Use of the polymer interface protection layer material according to claim 6 as a polymer interface protection layer of a high voltage lithium battery, characterized in that: The polymer interface protection layer material is applied to the surface of the electrode of the high-voltage lithium battery, and after drying, a solid polymer interface protection layer is formed on the surface of the electrode of the high-voltage lithium battery; The coating amount of the polymer interface protection layer material is 0.01-1 g / cm 2 ; The thickness of the solid polymer interface protection layer obtained after drying is 500nm-30μm.
Citation Information
Patent Citations
Protective film for lithium electrode, and lithium electrode and lithium secondary battery comprising same
US20180294513A1
Dendrite-Free, Wide Temperature Range Lithium Metal Batteries Enabled by Hybrid Network Ionic Liquids
US20220013807A1